2019
DOI: 10.1002/cche.10170
|View full text |Cite
|
Sign up to set email alerts
|

Effects of postsilking weak‐light stress on the flour quality of spring maize

Abstract: Background and objectives The low sunlight from June to July caused by cloudy weather in Southern China has a detrimental influence on the grain yield and quality of spring maize because this period overlaps with the grain filling stage. A field trial was conducted to study the effects of postsilking shading (30% and 50% light deprivation defined as moderate sunlight [MS] and severe shading [SS], respectively, and with plants under natural sunlight as the control) on grain weight, nutrient contents, pasting, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…In the present study, similar declines in PV, TV, FV, and P temp in flour were observed following two environmental LT stresses in both varieties (Table 1). Our previous study found that flour pasting properties are positively correlated with starch content in grains and negatively correlated with protein content and starch grain size (Wen et al, 2019), and this study also found similar results (Figure S2). The increase of protein content under LT stress will limit the swelling of starch in flour under heating, resulting in a decrease in flour pasting properties (Noisuwan et al, 2008).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, similar declines in PV, TV, FV, and P temp in flour were observed following two environmental LT stresses in both varieties (Table 1). Our previous study found that flour pasting properties are positively correlated with starch content in grains and negatively correlated with protein content and starch grain size (Wen et al, 2019), and this study also found similar results (Figure S2). The increase of protein content under LT stress will limit the swelling of starch in flour under heating, resulting in a decrease in flour pasting properties (Noisuwan et al, 2008).…”
Section: Discussionsupporting
confidence: 87%
“…The %R of SYN5 was higher than that of YN7 under LT treatment, indicating that the starch of YN7 is more dominant than SYN5 in retrograde tendency. The differences in the functional properties of SNY5 and YN7 grains may be related to their grain component content (Lu et al, 2014b;Wen et al, 2019). Therefore, the present study suggests that post-silking LT stress not only affects physiological and biochemical characteristics but also ultimately affects grain quality.…”
Section: Discussionmentioning
confidence: 65%
“…The mean starch content in 2019 (683 mg g −1 ) was higher than that in 2018 (645 mg g −1 ) because the grain development in 2019 1). 36,37 Starch granule size The size distribution of the starch granules presented typical bimodal profiles, with the percentage of small starch granules (d < 5 μm) ranging from 8.68% to 9.02% in 2018 and from 8.88% to 9.12% in 2019 (Fig. 3).…”
Section: Grain Starch Contentmentioning
confidence: 99%
“…However, the grain-filling stage is the key period affecting the yield and quality of waxy maize ( Lu et al., 2014 ). Weak-light stress during grain-filling stage led to yield reduction by reducing grain number and weight ( Yang et al., 2016 ; Shi et al., 2018 ; Wen et al., 2019 ), which posed a serious threat to the production safety of maize. Fresh waxy maize is the special maize with the largest planting area in China.…”
Section: Introductionmentioning
confidence: 99%